TOWARDS ARTIFICIAL INTELLIGENCE. POSSIBILITIES AND PSYCHO-PHILOSOPHICAL ISSUES. - Anyfantis, Ioannis (European Scientific Journal, ESJ, 2015)
During the last 30 years we all witnessed an incredible advance in digital technology. Modern technologies give us incredible computing power in our hands. Software development has provided intelligent ways of doing things. However, how far are we from the development of Artificial Intelligence machines? There are also of number of Psychological and Philosophical issues arisen by such attempts. Artificial Intelligence will be limited because we don’t fully understand the brain. Thus it is argued that until we can dissect the human mind accurately describe the various elements that make up our very being and consciousness, we cannot expect to artificially replicate intelligence.